Local Control by Radiofrequency Thermal Ablation Increased Overall Survival in Patients With Refractory Liver Metastases of Colorectal Cancer. Issue 14 (April 2016) - Yang, Po-Chih; Lin, Been-Ren; Chen, Yi-Chang; Lin, Yu-Lin; Lai, Hong-Shiee; Huang, Kai-Wen; Liang, Jin-Tung
Abstract : Abstract: Radiofrequency thermal ablation (RFA) is widely used for local solitary liver tumor control. However, the benefit of RFA for colorectal cancer with liver metastases, which is refractory to chemotherapy, remains unknown. We retrospectively enrolled 70 consecutive colorectal adenocarcinoma patients, who had synchronous liver metastases, who were refractory to chemotherapy, and whose life expectancy was >6 months, into this study to investigate the outcomes of RFA and associated prognostic factors. RFA was introduced to all of these patients during the enrollment. The time interval from RFA to recurrence of liver metastases and overall survival was recorded. Age, sex, carcinoembryonic antigen level, primary tumor location, postoperative adjuvant chemotherapy regimens, and the size and number of metastatic liver lesions were recorded. Cox regression analysis was used to determine the prognostic significance. Thirty-nine patients accepted RFA during chemotherapy, whereas 31 chose to receive chemotherapy alone. Patients with ≤5 and >5 liver metastases had median survival durations of 28 and 17 months, respectively ( P = 0.018). The dominant liver tumor size (<5 vs ≥5 cm) was significantly associated with median survival (30 vs 17 months, respectively; P = 0.038), as was the carcinoembryonic antigen level (35 vs 16 months for ≤200 vs >200 ng/mL respectively; P = 0.029). Besides, radiofrequency thermal ablation plus chemotherapy was associated with a better median overall survival than chemotherapy alone (29 vs 12 months, respectively; P = 0.002). In multivariate analysis, only radiofrequency thermal ablation treatment and number of liver tumors were significant prognostic factors for survival. Our result further revealed that patients treated with radiofrequency thermal ablation had longer progression-free intervals than those treated with chemotherapy alone (18 vs 9 months, respectively; P = 0.001). Hence, radiofrequency thermal ablation is a safe and effective adjunct treatment to chemotherapy.